Pelaksanaan Kegiatan Indonesia Creative Cities Festival (ICCF )Dan Cangkurah Expo Kota Banjarmasin - syafril, syafril; Fahmi, Muhammad; Fadilah, Neti Rosiana; Yuliani, Yuliani; Mohdari, Mohdari (LP3M Universitas Putra Bangsa, 2024)
This Community Service Activity is one of the Tri Dharma of Higher Education activities that must be carried out by a lecturer. This activity was held thanks to collaboration between the Banjarmasin City Regional Government, the Creative Economy Committee and the Indonesia Creative Cities Network (ICCN) as an organizational forum for creative cities. The implementation method used is a Seminar, Workshop and Tour Guide to Banjaarmasin City tourist attractions. Participants in this activity came from various cities throughout Indonesia which are members of the Creative Cities network and are also creative economy players. It is hoped that this Community Service activity will have a positive impact on the development of the creative economy and also economic growth in the City of Banjarmasin.